AGRIBISNIS TEMBAKAU DI INDONESIA: KONTROVERSI DAN PROSPEK (Forum Penelitian Agro Ekonomi, 2016)
Tobacco is one of the important commodities in Indonesia. The tobacco industry contributes significantly to the Indonesian economy, especially tax and excise as a source of government income, employment opportunity, source of income and regional development. However, tobacco and cigarettes has a negative impact on health and the environment. Indonesian cigarette industry is in a dilemma situation. Increasing public awareness about health and anti-smoking cigarettes causes a decrease of tobacco demand in the world and Indonesia, and its negative impact in the demand for tobacco leaf. This condition must be anticipated at the early stage with directive program in the development of tobacco crop substitution. This substitution can be carried out through the development of high value alternative crops with the application of technology and market assurances. Among these high value commodities are horticultural crops, like vegetables and ornamental plants.  To ensure market and the application of technology for such crops, it is necessary to develop a partnership relation with the market actors.   With a large number of smokers and a hereditary culture, Indonesia is considered as a potential market for the tobacco industry. This condition should allow a greater negative impact and social costs for Indonesia. To encounter such situation, Indonesia need a cigarette consumption reduction policy which could be applied through: (a) high cigarette tax and price, (b)  strictly abandon promotion, advertisement and cigarette sponsorship in various events that involve young people, and (c) well-guarded stipulation on free smoking area.